Antimicrobial activity against pathogenic bacteria, antioxidant and cytotoxic activity of cosmos caudatus - Sia, Yiik Swan; Chern, Zi Wei; Hii, Siew Ping; Tiu, Zi Bao; Mohd Azmir, Arifin (Penerbit Universiti Malaysia Pahang, 2021)
Cosmos caudatus is a traditional medicinal herb commonly found in Southeast Asia. This herb has been reported as a potential antioxidant and antimicrobial agent as it contains a variety of bioactive compounds.However, its cytotoxic effects on cancer still lack empirical evidence. Thus, this study aimed to investigate antimicrobial and antioxidant potentials of Cosmos caudatus as well as its cytotoxic effects on cancer cell lines. Ethanol and water extracts of Cosmos caudatus were tested for its antimicrobial activities against pathogenic bacteria, Staphylococcus aureus, Salmonella sp., Pseudomonas aeruginosa and Escherichia coli using agar well diffusion method. Antioxidant properties of the extracts were evaluated by 2,2-diphenyl-1-picryl-hydrazyl radical scavenging assay while cytotoxic activity of the extracts on colorectal carcinoma cell line, HCT 116 was determined by (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay. The findings indicated that conventional Soxhlet extraction with water as solvent extracted more efficiently than ethanolic maceration and ultrasonic assisted extraction. In antioxidants assay, both ethanolic and water extracts obtained through ultrasonic extraction exhibited the highest DPPH free radical scavenging capacity compared to maceration and Soxhlet extraction method. As for antimicrobial assay, both water and ethanol extracts showed no inhibitory action against the tested pathogenic bacteria. For anticancer activity, the F2, F7 and F8 fractions showed potent dose dependent cytotoxicity on HCT 116 cells with IC50 value of 15.53 ± 0.4, 32.72 ± 0.3 and 34.16 ± 1.4 μg/mL, respectively.